Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Untuk Meningkatkan Hasil Belajar Siswa Tentang Manusia dan Lingkungan Di Kelas V UPTD SD Negeri 55 - Yulia Yulia; Hasna Hasna; rahmat hidayat (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This research was motivated by the learning outcomes of five-grade students of UPTD SD Negeri 55 Parepare who had not yet reached the predetermined minimum learning completeness standard (SKBM). The research approach used is a qualitative approach and the type of research used is classroom action research. Based on the data obtained, the research results in the first cycle showed the learning process increased to good qualification (B) and the learning test results were in sufficient qualification (C) while in the second cycle the research results on the learning process increased to good qualification (B) and the learning test results are in good qualification (B). Based on the results of the study, it can be concluded that the application of the snowball throwing type of cooperative learning model can improve the learning process and student learning outcomes about human and environment in the five-grade of UPTD SD Negeri 55 Parepare.